Role of Family Communications in Adolescent Personal and Social Identity - Maulana Rezi Ramadhana; Ravik Karsidi; Prahastiwi Utari; Drajat Tri Kartono (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2019)
This study examines the relationship between family communication patterns (involving two dimensions of conversation and conformity) and the personal-social identity of adolescents. This study uses a survey technique involving 214 adolescents from intact families and single-parent families in one school in Bandung, by providing two scales of the Family Communication Pattern Revised (FCPR) from Ritchie and the scale of Social Identity-Personal Identity (SIPI) from Nario-Redmond. Data analysis to test three hypotheses in this study using Pearson product-moment correlation and regression analysis to find moderation of the measured variables. The findings indicate that the dimensions of the conversation are significantly positively related to social identity and personal identity. While the dimensions of conformity are negatively associated with social identity and positively associated with personal identity. After controlling for family status and sibling position in the family, the dimensions of conformity moderate significantly positive relationships between dimensions of conversation and social identity.